Prevalence and side effects of pediatric home tube feeding. Issue 1 (February 2019) - Krom, Hilde; van Zundert, Suzanne M.C.; Otten, Marie-Anne G.M.; van der Sluijs Veer, Liesbeth; Benninga, Marc Alexander; Kindermann, Angelika
Summary: Background & aims: Tube feeding ensures growth, but can have negative effects on health and psychosocial functioning, resulting in health related costs. The aims of this study were to determine the prevalence of pediatric home tube feeding in the Netherlands and to assess the clinical characteristics of tube fed children and side effects of tube feeding. Methods: The prevalence of pediatric home tube feeding was calculated using data (2010–2014) of both the Medicines and Devices Information Project of the National Health Care Institute, and Statistics Netherlands. Subsequently, a cross-sectional parental online questionnaire was used to obtain data regarding clinical characteristics of tube fed children and side effects of tube feeding. Children aged ≤17 years receiving tube feeding ≥2 weeks were included. Results: The prevalence of pediatric home tube feeding was 83–92:100, 000 children/year. Parents of 279 children (53% boys) completed the questionnaire. Most children (88%) had ≥1 medical diagnosis, of which congenital abnormalities (42%), perinatal problems (38%) and neurologic diseases (16%) were most common. They had gastrostomy (60%), nasogastric (33%), or other tube types (7%). Parents of most children (74%) mentioned ≥1 side effect due to tube feeding. Vomiting (37%), lack of appetite (29%), and gagging (29%) were reported most frequently. Nasogastric tube placement resolved in negative experiences (94%). Conclusions: The prevalence of pediatric home tube feeding varies between 83 and 92:100, 000 children/year in the Netherlands. These children are characterized by various underlying medical diagnoses. Side effects of tube feeding are frequently reported by parents. Further studies should focus on methods reducing side effects.